Rapid learning of pursuit target motion trajectories revealed by responses to randomized transient sinusoids - Graham R. Barnes (Bern Open Publishing, 2012)
When humans pursue sinusoidal target motion they rapidly learn to track with minimal phase error despite inherent visuo-motor processing delays; prior evidence suggests that prediction might even occur within the first cycle. Here, this has been examined by evoking reactive responses to single cycle stimuli having randomised periodicity and peak velocity. Periodicity was varied within three specific ranges with differing average periodicity. Initial responses in the first half-cycle were remarkably similar within periodicity ranges, irrespective of target velocity or frequency, but differed between ranges. In contrast, in the second half-cycle eye velocity closely matched the target in velocity and timing, irrespective of differences in eye velocity in the first half. Abrupt transitions occurred between first and second half-cycles, consistent with the hypothesis that target motion information is sampled and stored within the first half-cycle, irrespective of actual eye velocity evoked, and then released as a predictive estimate in the second half.